Exploring ChatGPT’s Voice Speech Recognition and Real-Time Feedback Features to Enhance EFL Speaking Skills: A Systematic Literature Review - Daniel Urslenton Wiser Sumang; Margana; Dyah Setyowati Ciptaningrum (Universitas Islam Negeri Palopo, 2026)
This study examines the integration of ChatGPT's voice recognition and real-time feedback features in enhancing EFL students' speaking skills through a systematic literature review that was conducted through identification, analysis, and synthesis. Ten peer-reviewed articles published between 2022 and 2025 were selected based on specific inclusion criteria, with a focus on AI-powered tools that support the development of EFL speech. Thematic analysis revealed that most of the research emphasized the effectiveness of AI-based voice-enabled platforms and feedback in improving learners' pronunciation, fluency, and engagement in English speaking skills. Some tools use machine learning algorithms to personalize feedback, while others promote autonomous speaking practices through interactive conversational interfaces. The findings also identify challenges such as recognition accuracy and pedagogical implementation gaps. These results show that ChatGPT and similar technologies strongly offer meaningful support for speaking instruction when carefully integrated into the EFL learning environment.